Ергоніми відонімного походження в комунікативному просторі міста Луцька: структурно-семантичні особливості - Горожанов, Юрій; Horozhanov, Yuriy (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано стан дослідження ергонімів у вітчизняному та російському мовознавстві, звернено увагу на термінологічну неусталеність у номінації цієї групи пропріальної лексики, визначено структурно-семантичні особливості ергонімів м. Луцька. З’ясовано, що в комунікативному просторі м. Луцька найбільш поширені ергоніми відантропонімного походження. The article analyzes the study ergonims in domestic and Russian linguistics, drawn attention to the terminological instability in ergonims, identified structural and semantic features ergonims Lutsk. The article analyzes the research of ergonims in Ukrainian and Russian linguistics, drawn attention to the terminological instability in ergonims, identified structural and semantic features ergonims Lutsk. It was found that onims ergonims most often found in urban communication space. An analysis of the scientific literature shows that researchers propose terms such as ergonim, urbonim, urbanonim, ktematonim, firmonim, oykodomonim, mikrotoponim. The author uses the traditional term ergonim. Among onims ergonims recorded in Lutsk, is dominated by educated antroponims (mainly as a basis for the name is taken, sometimes – the surname). More likely to use female names, rarely – men’s names, as well as fixed structure with a preposition at. In addition, the nominator used by other groups of onims for naming companies – toponims (makrotoponims, polisonims, hydronyms) theonims and mifonims.
Ergonims of onims origin in the communicative space of Lutsk: structural and semantic features
Keywords: ергонім; ергонімія; ергоурбонім; фірмонім; комунікативний простір; відонімні ергоніми; ergonims; ergourbonims; firmonims; communicative space; ergonims of onims origin